2020
DOI: 10.1177/0896860819894066
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life on combination therapy with peritoneal dialysis and hemodialysis in comparison with hemodialysis and peritoneal dialysis: A cross-sectional study

Abstract: Background: The health-related quality of life (HRQOL) of dialysis patients has not been well examined, especially in combination therapy with peritoneal dialysis and hemodialysis (PD+HD) patients. We compared the HRQOL of PD+HD patients with that of HD and PD patients. Methods: A multicenter, cross-sectional study was conducted on 36 PD+HD, 103 HD, and 90 PD patients in Japan who completed the Kidney Disease Quality of Life Short Form 36, version 1.3. HRQOL scores were summarized into physical- (PCS), mental-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…In 2008, differences in QOL were compared between 77 in-center HD and 58 CAPD/PD patients, and the study concluded that patients on HD experienced more compromised QOL compared to those on CAPD/PD [12]. e same results were supported later by more recent trials [13][14][15]. However, some other trials concluded that depression is highly more prevalent in patients on PD than in those on HD [16].…”
Section: Discussionmentioning
confidence: 98%
“…In 2008, differences in QOL were compared between 77 in-center HD and 58 CAPD/PD patients, and the study concluded that patients on HD experienced more compromised QOL compared to those on CAPD/PD [12]. e same results were supported later by more recent trials [13][14][15]. However, some other trials concluded that depression is highly more prevalent in patients on PD than in those on HD [16].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we reported that PDþHD may have a similar profile of health-related quality of life to PD and have an advantage in role and social participation as compared with HD. 27 PD and HD combination may be an individualized dialysis modality and a treatment of choice in patients with ESRD with decreased RKF who prefer PD lifestyles for social, economic, or geographic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-two PDþHD patients were matched with 42 HD patients with 1:1 matching for age and diabetic nephropathy among the entire cohort (Figure 1), in which we previously investigated health-related quality of life among PDþHD, HD, and PD patients. 27 The exclusion criteria of the study were as follows: patients younger than 20 years; those who changed their dialysis modality or were hospitalized within 1 month; those without a decision-making ability due to cognitive impairment; those with severe frailty or a life expectancy of less than 6 months. PDþHD patients receiving 2 or more HD sessions per week and HD patients receiving other than 3 HD sessions per week were also excluded.…”
Section: Patientsmentioning
confidence: 99%
“…PD+HD had a close profile of the health-related quality of life of PD, which was better than HD especially in role and social domains. 15 Fluid status of PD+HD was also relatively good as compared with that of HD and PD. 25 Furthermore, totalhospitalization risk was similar between PD+HD and HD, although PD+HD may have a higher hospitalization risk of dialysis access-related complications than HD.…”
Section: Discussionmentioning
confidence: 91%